Knowledge and Family Support on Anxiety Of Chronic Kidney Disease Patients Undergoing Hemodialyzed During The Covid-19 Pandemic : A Cross Sectional Study - Lina, Liza Fitri; Safitri, Alvistiqomah Riani; Eva Oktavidiati; Efrisnal, Dodi; Arifah, Siti (Jurnal Berita Ilmu Keperawatan, 2025)
Hemodialysis is a frequent treatment for patients with chronic kidney disease (CKD), which causes anxiety. The level of anxiety is determined by various factors, including age, knowledge, environment, duration of hemodialysis, and family support. The study aims to investigate the elements that influence patients' anxiety about hemodialysis during the COVID-19 epidemic. This cross-sectional study included 54 patients on hemodialysis at M. Yunus Hospital in Bengkulu. The sample was collected using the purposive sampling technique. Anxiety was measured using a collection of questionnaires, including the Gutman and Likert scales. Data indicated that a majority of patients were females 28 (52.0%), most of them had a diploma education 21 (38.9%), housewives dominated the job 14 (26.0%), more patients were married 26 (48.0%), and the majority of them were Muslim 51 (94.4%). The Pearson chi-square test showed that knowledge and family support influenced patients’ anxiety with a p-value of 0.026 and 0.000, respectively. The level of information and family support had an impact on the anxiety of CKD patients undergoing hemodialysis during the Covid-19 epidemic. Research on enhancing knowledge of disease signs, treatment methods, and the value of morning exercise for hemodialysis patients during the COVID-19 pandemic is urgently needed